2011
DOI: 10.1177/039463201102400409
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Plasma Levels and Coronary Artery Disease: A New Possible Biomarker of Acute Coronary Syndrome

Abstract: Inflammation plays a key role in atherosclerosis. Galectin-3 is a macrophage- and endothelium-derived mediator actively involved in the regulation of many aspects of inflammatory cell behaviour. The aim of this study is to quantify plasma Galectin-3 in patients with coronary artery disease (CAD) and different clinical manifestation at the moment of observation in order to verify whether Galectin-3 could be a useful biomarker of atherosclerotic state. We enrolled 125 patients affected by CAD, angiographically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 29 publications
6
55
0
5
Order By: Relevance
“…Data from the Pravastatin or Atorvastatin Evaluation and Infection Therapy-Thrombolysis In Myocardial Infarction 22 trial (PROVEIT-TIMI 22) demonstrated that galectin-3 values above 16.7 µg/L (median), measured within 7 days after acute coronary syndrome, was significantly associated with higher risk of HF development during 2-year follow--up, but elevated levels of this biomarker were observed mostly in patients with hypertension, diabetes, prior HF and prior MI [16]. Falcone et al [17] analyzed a group of patients with angiographically documented coronary artery disease: unstable patients (n = 55) had higher galectin-3 levels in comparison to the stable subjects (27.75 ng/mL vs. 6.48 ng/mL, p < 0.001). Compared with these studies, we observed lower galectin-3 concentrations in our group of patients (median 13.0 ng/mL), which could be explained by our restrictive inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Pravastatin or Atorvastatin Evaluation and Infection Therapy-Thrombolysis In Myocardial Infarction 22 trial (PROVEIT-TIMI 22) demonstrated that galectin-3 values above 16.7 µg/L (median), measured within 7 days after acute coronary syndrome, was significantly associated with higher risk of HF development during 2-year follow--up, but elevated levels of this biomarker were observed mostly in patients with hypertension, diabetes, prior HF and prior MI [16]. Falcone et al [17] analyzed a group of patients with angiographically documented coronary artery disease: unstable patients (n = 55) had higher galectin-3 levels in comparison to the stable subjects (27.75 ng/mL vs. 6.48 ng/mL, p < 0.001). Compared with these studies, we observed lower galectin-3 concentrations in our group of patients (median 13.0 ng/mL), which could be explained by our restrictive inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the most common finding among such investigations is that circulating Gal-3 levels are elevated in ACS/AMI, being released during the acute phase of AMI [31,[33][34][35][36][37][38][39]. Indeed, Gal-3 could be part of a survival mechanism of the injured myocardium to cope with the ischemic insult [14].…”
Section: Gal 3 In Acsmentioning
confidence: 99%
“…Wilcoxon-próbát alkalmaztunk a felvételkori és a később (6 órán belül) elvégzett hsTn-mérés eredményeinek összehasonlítására. Beszédzavar (1) Apoplexia cerebri (1) Eszméletvesztés (35) AMI (3), delirium tremens (1), epilepszia (3), exsiccosis (1), hyperglikaemiás ketoacidosis (3), hypoglikaemia (2), ictus caloris (1), sokk (2), collapsus (2), pancreatitis acuta (2), fi brillatio auricularis (4), rhabdomyolysis (3), apoplexia cerebri (3), arrhythmia cardiaca (2), embolia pulmonum (2), infarctus cerebri (1) Fejfájás (2) Cephalalgia (1), hypertonia (1) Fulladás (30) Bronchitis acuta (5), COPD (1), hydrothorax (2), bronchitis chronica (1), decompensatio cardiaca (9), fi brillatio auricularis (3), pneumonia (4), neoplasma pulmonum malignum (2), oedema pulmonum (3) Gyengeség (20) Infarctus cerebri (1), cholecystitis (1), exsiccosis (2), anxietas (1), TIA (15) Hányás (3) Gastritis acuta (1), subileus (2) Hasfájás (5) Exsiccosis (1), hyperaciditas (1), pancreatitis acuta (1), szeptikus sokk (2) Lábduzzadás (5) MVT (2) [5]. Az AMI bekövetkezte utáni praenecrosis-és necrosis-biomarkerek koncentrációjának változását mutatja a 3. ábra.…”
Section: Statisztikai Elemzésunclassified
“…A prognosztikai markerek (oldható OX40 ligand, MPO, rezisztin, oldható ST2 fehérje) egy esetleg későbbi időpontban bekövet-kező AMI valószínűségét jelzik [6,16,17,18]. A plakkmarkerek (visfatin, galectin-3, oldható lectinszerű oxidált LDL-receptor-1, lipoproteinasszociált foszfolipáz-A2, leukotrién-B4, extracelluláris mátrixmetalloproteináz, triptáz, oldható LR11 fehérje, oldható amyloid prekurzor fehérje 770, apelin, chitotriosidas, tenascin-C) az instabilitást, a sérülés bekövetkeztét, mértékét mutatják, így utalva az AMI lehetőségére [19,20,21,22,23,24,25,26,27,28,29,30]. Ígéretes korai markernek tűnik az ischaemiamodifi kált albumin, a hősokkfehérje-27, a katepszin-K, a C1q-kötő adiponectin, a sejtmentes keringő DNS, a májsejt-növekedési faktor, a glikogén foszforiláz BB izoenzim és a növekedést elkülönítő faktor 15 [31,32,33,34,35,36,37,38,39].…”
Section: Statisztikai Elemzésunclassified